The Orion Nebula : where stars are born - O'Dell, C. Robert (Charles Robert), 1937- (Belknap Press of Harvard University Press, 2003)
The glowing cloud in Orion's sword, the Orion Nebula is a thing of beauty in the night sky; it is also the closest center of massive star formation--a stellar nursery that reproduces the conditions in which our own Sun formed some 4.5 billion years ago. O'Dell has spent a lifetime studying Orion, and in this book he explains what the Nebula is, how it shines, its role in giving birth to stars, and the insights it affords into how common planet formation might be. To help his readers appreciate the Nebula and its secrets, O'Dell unfolds his tale chronologically, as astrophysical knowledge developed, and our knowledge of the Nebula and the night sky improved.